2006
DOI: 10.1016/j.alcohol.2007.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of serotonin-3 receptors increases dopamine release within the ventral tegmental area of Wistar and alcohol-preferring (P) rats

Abstract: The objectives of the present study were to examine (a) the effects of activating serotonin-3 (5-HT 3 ) receptors on dopamine (DA) release in the anterior and posterior ventral tegmental area (VTA) of Wistar rats; and (b) determine if there are differences in 5-HT 3 -stimulated DA release in the VTA between alcohol-preferring (P) and Wistar rats. Local perfusion with the 5-HT 3 agonist 1-(mchlorophenyl)-biguanide (CPBG) in the anterior and posterior VTA stimulated DA release in the both regions. The CPBG-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…Indeed, 5-HT 3 binding was detected in the rat VTA using [ 3 H]quipazine (Perry, 1990), whereas studies using more selective ligands with a higher affinity than quipazine did not identify the presence of 5-HT 3 -binding sites in the rat VTA (Barnes et al, 1990 ;Hamon, 1992 ;Laporte et al, 1992). Nonetheless, local perfusion of the 5-HT 3 receptor agonist m-chlorophenyl-biguanide in the VTA, via a microdialysis probe, induces a dosedependent increase in extracellular level of DA (Campbell et al, 1996 ;Liu et al, 2006). Therefore very scarce 5-HT 3 receptors possibly present in the VTA might still be functionally important.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, 5-HT 3 binding was detected in the rat VTA using [ 3 H]quipazine (Perry, 1990), whereas studies using more selective ligands with a higher affinity than quipazine did not identify the presence of 5-HT 3 -binding sites in the rat VTA (Barnes et al, 1990 ;Hamon, 1992 ;Laporte et al, 1992). Nonetheless, local perfusion of the 5-HT 3 receptor agonist m-chlorophenyl-biguanide in the VTA, via a microdialysis probe, induces a dosedependent increase in extracellular level of DA (Campbell et al, 1996 ;Liu et al, 2006). Therefore very scarce 5-HT 3 receptors possibly present in the VTA might still be functionally important.…”
Section: Discussionmentioning
confidence: 90%
“…Although the cellular localization of these receptors remains unknown, activation of 5-HT 3 receptors in the posterior VTA produces a stimulatory net effect on local dopamine neurons (Liu et al, 2006). A previous electrophysiological study indicated that EtOH at doses of 1 to 25 mM (approximately 5-110 mg%) induced a 5 to 20% increase of 5-HT 3 receptor-mediated ion currents in vitro (Lovinger and White, 1991).…”
Section: Icsa Of Etoh Andmentioning
confidence: 99%
“…The DRN has projections into numerous brain regions, including the mesolimbic regions important in reward and addiction (amygdala, hippocampus, caudate putamen, substantia nigra and ventral tegmental area). Projections from the raphe nuclei mediate dopamine release in the ventral tegmental area (Liu et al, 2006b; Rodd et al, 2007; Sari et al, 2011). Ethanol-naïve P rats have fewer serotonergic neurons in the DRN than ethanol-naïve NP rats and decreased serotonergic projections into terminal regions (Zhou et al, 1994).…”
Section: Introduction/backgroundmentioning
confidence: 99%